Cisplatin Inhibition of Anthrax Lethal Toxin - Moayeri, Mahtab (American Society for Microbiology, 2006)
Bacillus anthracis lethal toxin (LT) produces symptoms of anthrax in mice and induces rapid lysis of macrophages derived from certain inbred strains. LT is comprised of a receptor binding component, protective antigen (PA), which delivers the enzymatic component, lethal factor (LF), into cells. We found that mouse macrophages were protected from toxin by the antitumor drug cis-diammineplatinum (II) dichloride (cisplatin). Cisplatin was shown to inhibit LT-mediated cleavage of cellular mitogen-activated protein kinases (MEKs) without inhibiting LF's in vitro proteolytic activity. Cisplatin-treated PA lost 100% of its ability to function in toxicity assays when paired with untreated LF, despite maintaining the ability to bind to cells. Cisplatin-treated PA was unable to form heptameric oligomers required for LF binding and translocation. The drug was shown to modify PA in a reversible noncovalent manner. Not surprisingly, cisplatin also blocked the actions of anthrax edema toxin and of LF-Pseudomonas aeruginosa exotoxin A fusion peptide (FP59), both of which require PA for translocation. Treatment of BALB/cJ mice or Fischer F344 rats with cisplatin at biologically relevant concentrations completely protected the animals from a coadministered lethal dose of LT. However, treatment with cisplatin 2 hours before or after animals received a lethal bolus of toxin did not protect them.